Influence of statin potency and liposolubility on Alzheimer's disease patients: A population-based study - Mar García-Zamora; Gemma García-Lluch; Lucrecia Moreno; Juan Pardo; Consuelo Cháfer - Pericás (Elsevier, 2024)
Although Alzheimer's disease (AD) cause is still unknown, there are several known risk factors, such as dyslipidemia. Statins are the most prescribed lipid-modifying therapies. Recent research has suggested a relationship between statins and AD, nevertheless, their ability to prevent AD is still unclear. Therefore, this cross-sectional study aimed to examine the relationship between statin use and anti-AD drug prescription. For that purpose, a database containing information on medications prescribed to patients aged 50 years or older (n = 233183) between 2018 and 2020 was used. Defined daily doses (DDDs) were calculated according to the ATC/DDD index 2023. Statistical analyses, with logistic regression and cumulative incidence, were carried out to assess statins and anti-AD drug consumption. As a result, a total of 47852 patients aged more than 70 years who were prescribed at least one antihypertensive, antidiabetic or lipid-modifying agent were included in the study. Of these, 45345 patients were classified within the cardiovascular risk group and 2483 were classified as patients with only hyperlipidemia. Patients using low-potency or hydrophilic statins had lower odds of anti-AD usage when compared to high-potency or lipophilic statins, respectively. Similarly, rosuvastatin and pitavastatin had lower odds of anti-AD medication intake when compared to atorvastatin. Finally, pitavastatin DDDs were prone to lower the odds of anti-AD medication usage when compared to rosuvastatin. In conclusion, a potential association between statins and the intake of AD medication has been observed. Specifically, low-potency (pitavastatin) and hydrophilic (rosuvastatin) statins were associated with less use of anti-AD medication.